A Case of Erythema Multiforme Major Developed after Sequential Use of Two Immune Checkpoint Inhibitors, Nivolumab and Ipilimumab, for Advanced Melanoma: Possible Implication of Synergistic and/or Complementary Immunomodulatory Effects - Akira Utsunomiya; Noritaka Oyama; Shiro Iino; Natsuki Baba; Takenao Chino; Natsuko Utsunomiya; Minoru Hasegawa (Karger Publishers, 2018)
Immune checkpoint inhibitors, such as ipilimumab and nivolumab, reverse the imbalance of antitumor self-tolerance and enhance T-cell responses. Currently, ipilimumab and nivolumab have a reported therapeutic impact on unresectable or metastatic melanomas; however, they also induce immune-related adverse events (irAEs). Ipilimumab-induced cutaneous irAEs are mostly low grade and manageable, although all-grade rash may occur in approximately 45% of all patients. We here report the case of a young woman with erythema multiforme major, which developed after sequential use of these 2 immune checkpoint inhibitors for advanced melanoma of the scalp. Initially, she received 12 cycles of nivolumab monotherapy followed by ipilimumab. A week later, multiple erythematous papulo-erythemas appeared on almost her entire body, with high-grade fever, mucosal involvements, and dyspnea. Immunohistochemistry using the lesioned skin revealed lymphocytic infiltration predominantly positive for CD8, contrasting with those for CD4 and Foxp3. Ipilimumab was stopped but she continued to receive empirical antibiotics; additionally, she was treated with intravenous steroid pulse therapy and immunoglobulin, followed by oral prednisolone. Her symptoms subsided rapidly, allowing a restart of nivolumab monotherapy alone. In our case, the long-standing preceding nivolumab monotherapy may synergistically and/or complementary have contributed to - in combination with the later administration of ipilimumab - recover antigen-responsive T-cell immunity, which is similar to the concept of immune reconstitution inflammatory syndrome, resulting in the establishment of an underlying immunopathology of erythema multiforme and life-threatening airway obstruction.